MicroRNA-21-3p modulates FGF2 to facilitate influenza A virus H5N1 replication by refraining type I interferon response. Issue 5 (28th May 2020) - Shi, Jianli; Feng, Ping; Gu, Tingting
Abstract: Background: Influenza A virus (IAV) has greatly affected public health in recent decades. Accumulating data indicated that host microRNAs (miRNAs) were related to IAV replication. The present study mainly focused on the effects of microRNA-21-3p (miR-21-3p) on H5N1 replication. Methods: The levels of miR-21-3p, virus structural factors (matrix 1 (M1), nucleoprotein (NP)), type I interferon (IFN) response markers (IFN-β, IFN-α), IFN-stimulated genes (protein kinase R (PKR), myxovirus resistance A (MxA), 2′-5′-oligoadenylate synthetase 2 (OAS)), and fibroblast growth factor 2 (FGF2) were measured by quantitative real-time polymerase chain reaction (qRT-PCR). The protein levels of M1, NP, and FGF2 were tested by Western blot assay. The virus titer was assessed by tissue culture infective dose 50% (TCID50 ) assay. The dual-luciferase reporter assay and ribonucleic acid (RNA) immunoprecipitation (RIP) assay were used to verify the interaction between miR-21-3p and FGF2. Results: MiR-21-3p was reduced in H5N1-infected patients and A549 cells. MiR-21-3p overexpression facilitated the levels of M1, NP, TCID50 value, and reduced the levels of IFN-β, IFN-α, PKR, MxA, and OAS in H5N1-infected A549 cells. FGF2 was verified as a direct target of miR-21-3p. The introduction of FGF2 counteracted miR-21-3p-mediated decrease in the levels of M1, NP, and TCID50 value, as well as reduction in the levels of IFN-β, IFN-α, PKR, MxA, and OAS in H5N1-infected A549 cells. Conclusion: MiR-21-3p down-regulated FGF2 expression to accelerate H5N1 replication and confine IFN response.